Common vampire bat attacks on humans in a village of the Amazon region of Brazil Agressões de morcegos hematófagos a pessoas em um povoado da região amazônica do Brasil - Maria Cristina Schneider; Joan Aron; Carlos Santos-Burgoa; Wilson Uieda; Sílvia Ruiz-Velazco (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
Many people in Amazonian communities have reported bat bites in the last decade. Bites by vampire bats can potentially transmit rabies to humans. The objective of this study was to analyze factors associated with bat biting in one of these communities. A cross-sectional survey was conducted in a village of gold miners in the Amazonian region of Brazil (160 inhabitants). Bats were captured near people's houses and sent to a lab. Of 129 people interviewed, 41% had been attacked by a bat at least once, with 92% of the bites located on the lower limbs. A logistic regression found that adults were bitten around four times more often than children (OR = 3.75, CI 95%: 1.46-9.62, p = 0.036). Males were bitten more frequently than females (OR = 2.08, CI 95%: 0.90-4.76, p = 0.067). Nine Desmodus rotundus and three frugivorous bats were captured and tested negative for rabies. The study suggests that, in an area of gold miners, common vampire bats are more likely to attack adults and males. The control strategy for human rabies developed in this region should therefore place special emphasis on adult males. There should also be more research on how the search for gold in the Amazonian region places people and the environment at risk. Agressões de morcegos a pessoas vêm sendo notificadas em várias comunidades amazônicas nesta última década. Isto constitui um risco potencial para a raiva humana transmitida por morcegos. O objetivo deste estudo foi de analisar fatores associados a estas agressões em uma destas comunidades. Foi realizado um estudo transversal em um povoado de garimpeiros na Região Amazônica brasileira (160 habitantes). Foi realizada a captura de morcegos junto às casas e foram enviadas amostras para o laboratório. Das 129 pessoas entrevistas, 41% foram agredidas por morcegos pelo menos uma vez, com 92% das mordidas localizadas nos dedos dos pés. Por meio de regressão logística, encontrou-se que adultos eram agredidos ao redor de quatro vezes mais do que crianças (OR = 3,75, IC: 1,46-9,62, p = 0,036). Homens foram agredidos com maior freqüência do que mulheres (OR = 2,08, IC: 0,90-4,76, p = 0,067). Nove Desmodus rotundus e três morcegos frugívoros foram capturados e resultaram negativos para a raiva. O estudo sugere que, em áreas de garimpo, adultos do sexo masculino têm maior probabilidade de serem agredidos por morcegos. As ações de controle para a raiva humana a serem desenvolvidas nestes lugares devem dar ênfase especial a adultos homens. Recomendam-se mais investigações sobre o modo como o garimpo na Região Amazônica está colocando em risco as pessoas e o ambiente.